Modelo de gerenciamento de resíduos da Construção Civil (RCC) apoiado pelo método Analytic Hierarchy Process (AHP) - Direitinho, Romão Manuel Leitão Carrapato (2020)
The main problem situations faced by cities, almost twenty years after the implementation of CONAMA Resolution No. 307/2002, which came to regulate the main stages of the management of RCC's, continue to be related to inadequate destinations of huge quantities produced of these residues. Much has been done since then to improve this type of situation in the country. However, most academic research on the subject almost always addresses this issue from a public, municipal perspective, which of course is different from the perspective of private builders, not least because there is a line of profit break to separate them. In this sense, more than a survey was concerned with developing computer tools to support the municipal management of RCC's. Contrary to what happens for private agents (construction companies). This thesis comes in some way to bridge this gap, with the development of two free programs (one based on the MMAD AHP), and an empirical mathematical model, which work together to try to optimize the management of RCC's produced on construction sites of vertical multifamily buildings, and to assist Brazilian private builders.